Additional jump interval training as a form of warm-up on enhancing aerobic capacity, muscular strength, and power in female dancers: a cohort study - Sun, Qianqian; Wu, Mingzhu; Ni, Yike (Frontiers in Physiology, 2025)
ObjectivesThis study aimed to compare the effects of jump interval training (JIT) as a supplement to a warm-up with a control group that continued their regular warm-up routine, on the development of aerobic capacity, maximal isometric strength, and vertical jump power in female dancers over a 6-month period.MethodsFifty-five female sport dancers (aged 16.2 ± 0.9 years) were monitored throughout the 6 months, with evaluations conducted at baseline, 3 months, and 6 months. Aerobic capacity was assessed using the multistage fitness test (MFT), while muscular assessments included squat jump (SJ), countermovement jump (CMJ), and isometric mid-thigh pull test (IMTP) measured on force platforms. The participants were analyzed into two cohorts: one group adhered to the JIT warm-up, which involved three sets of 30-s bilateral squat jumps during the potentiation phase, while the control group (TWU) performed ballistic dance movements emphasizing explosive techniques, such as rapid leaps and forceful limb movements, in the same phase.ResultsAfter 6-months, significant differences were observed between groups in IMTP (F = 8.702; p = 0.005; d = 0.796, moderate effect size), SJ (F = 5.454; p = 0.023; d = 0.637, moderate effect size), CMJ (F = 5.921; p = 0.018; d = 0.659, moderate effect size), and MFT (F = 52.370; p < 0.001; d = 1.950, large effect size).ConclusionThe study concludes that incorporating JIT exercises into warm-up routines significantly enhances aerobic capacity and muscular performance over 6 months, with early improvements in aerobic capacity and noticeable benefits in muscular performance such as SJ peak force, CMJ peak power, and IMTP peak force after three and 6 months. This study contributes to the field as one of the few that demonstrates the relevance and practicality of integrating microdosing (i.e., small but intensive JIT sessions throughout the week) into dance warm-up routines.